Coverable BaTiO3-Fe3O4 catalytic material with excellent performance as well as preparation method and application thereof

The BaTiO3@Fe3O4 composite material is prepared by the hydrothermal method, which solves the problem of low removal efficiency of refractory organic pollutants in the existing technology, achieves efficient degradation, easy recycling of materials, and low cost, and is suitable for industrial production.

CN119327463APending Publication Date: 2025-01-21FUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411680632.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art has low efficiency in removing difficult-to-degrade organic pollutants in water treatment, and the preparation process is complex and costly, making it difficult to meet the needs of industrial production.

Method used

Batio3@Fe3O4 composite materials are prepared by water thermal method. By growing a nuclear shell structure by growing titanium oxide on the original position on titanic acid pink, the preparation process is simplified and catalytic performance is improved.

Benefits of technology

Efficient degradation of organic dyes is achieved, the degradation rate is significantly increased, and the material is easy to recycle and has low cost, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327463A_ABST
    Figure CN119327463A_ABST
Patent Text Reader

Abstract

The invention discloses a recoverable BaTiO3atFe3O4 catalytic material with excellent performance and a preparation method and application thereof, the material has a core-shell structure, has excellent catalytic performance under the action of simulated sunlight and mechanical energy, can completely degrade a 5ppm rhodamine B solution within 9 minutes, and the degradation rate reaches 0.48 min <-1 >; the material is environment-friendly, easy to recycle and reusable. The material is wide in applicability, has an excellent catalytic effect under different pH values and different pollutant environments, and is simple in preparation process, low in material cost and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysis and piezoelectric catalysis, and in particular to a BaTiO3@Fe3O4 catalytic material with excellent performance and recyclability, and a preparation method and application thereof. Background Art

[0002] Many regions around the world are facing the challenge of water pollution, including rivers, lakes, groundwater and oceans. Industrial wastewater, agricultural discharge, domestic sewage, etc. have caused serious pollution to water bodies. Many factories produce a large amount of wastewater during the production process. These wastewaters often contain various organic substances and other harmful substances. If they are discharged directly without treatment, they will cause serious pollution to water bodies. Pollution will lead to the death of aquatic organisms and the destruction of ecosystems, leading to a reduction in biodiversity.

[0003] Barium titanate, as a piezoelectric semiconductor material, has excellent piezoelectric properties. During the water treatment process, when subjected to mechanical forces such as water flow, vibration or ultrasound, polarized charges will be generated inside barium titanate, thereby forming an electric field. This electric field can accelerate the chemical reaction on the surface of the material and improve the catalytic efficiency. It can achieve rapid degradation of pollutants in water, especially the removal of difficult-to-degrade organic pollutants. Barium titanate can absorb light energy and generate photogenerated electron and hole pairs under light conditions. These photogenerated carriers are highly reactive and can trigger a series of redox reactions. Photocatalysis can degrade organic pollutants in water and improve the purification effect of water quality. The Fenton reaction is an efficient oxidation process that can catalyze the production of hydroxyl radicals (·OH) with extremely strong oxidizing properties, thereby effectively oxidizing and degrading pollutants. This reaction usually involves iron-containing substances (such as ferroferric oxide) as catalysts, which work together with hydrogen peroxide (H2O2) to produce hydroxyl radicals to degrade organic matter.

[0004] Invention patent CN113441145A introduces a preparation method of barium titanate / iron oxyhydroxide photocatalyst, which uses H2Ti2O5, BaTiO3, FeCl3·6H2O, NH4HCO3 and other raw materials to prepare BaTiO3 / FeOOH heterojunction photocatalyst. The degradation rate of the catalyst under simulated sunlight and by adding H2O2 to degrade the organic dye Rhodamine B is only 0.23min -1 . Compared with the present invention, the patent 1) needs to add H2O2, which is more expensive and has a lower degradation rate in actual production applications; 2) the preparation method introduced in the patent requires the preparation of H2Ti2O5 solution first, then the preparation of BaTiO3 powder, and finally the synthesis of BaTiO3 / FeOOH. Compared with the present invention, the patent only needs to prepare BaTiO3 powder and then synthesize BaTiO3@Fe3O4 in two steps, which greatly shortens the preparation process, preparation time and preparation cost.

[0005] Invention patent CN117942997A introduces a preparation method and application of BaTiO3 / GDY / Au piezoelectric enhanced photocatalyst. The invention requires HAuCl4·3H2O raw material in the preparation, which is expensive and has a complicated preparation process.

[0006] Wang et al. synthesized BaTiO3 / ZnO heterojunction catalysts by sol-gel method. In this study, the oxidative decomposition of methylene blue (MB) dye was used as a model reaction. When the BaTiO3:ZnO ratio was 1:1, a 100% MB degradation rate was observed after 40 min of catalytic degradation (Wang Y, Liu L, Zhao W, et al. Spontaneous polarisation of ferroelectric BaTiO3 / ZnO heterostructures with enhanced performance in a Fenton-like catalytic reaction[J]. Ceramics International, 2022, 48(2): 2726-2735. DOI: 10.1016 / j.ceramint.2021.10.059.).

[0007] Fu et al. used hydrothermally synthesized single-crystalline BaTiO3 nanoparticles to prepare BaTiO3@TiO2 nanofibers by sol-gel assisted electrospinning and annealing. The piezoelectric photocatalytic degradation rate constant (k) of BaTiO3@TiO2 nanofibers for methyl orange (MO) reached 0.1484min under the synergistic piezoelectric photocatalysis of ultrasound and ultraviolet irradiation. -1 . (Fu B, Li J, Jiang H, et al. Enhanced piezotronics by single-crystalline ferroelectrics for uniformly strengthening the piezo-photocatalysis of electrospun BaTiO3@TiO2nanofibers[J]. Nanoscale, 2022, 14(38): 14073-14081.).

[0008] Mushtaq et al. prepared CoFe2O4 by a hydrothermal method, and then formed a BFO shell through sol-gel technology to obtain a CFO@BFO core-shell structure. They used the energy of ultraviolet-visible light, ultrasound and magnetic field to successfully degrade RhB pollutants. The degradation rate of RhB dye was 99% within 1 hour (Mushtaq F, Chen X, Torlakcik H, et al. Enhanced catalytic degradation of organic pollutants by multi-stimuli activated multiferroic nanoarchitectures[J]. Nano Research, 2020, 13: 2183-2191.).

[0009] Zhang Sen et al. added barium titanate powder and ferrous sulfate solution to carbamazepine (CBZ) solution and used the piezoelectric-Fenton effect to degrade CBZ. The degradation rate reached 99% after 90 minutes, and the first-order reaction rate constant was 0.02598 min -1 . (Zhang Sen. Low-frequency ultrasound drives BaTiO3 piezoelectric-Fenton system to degrade carbamazepine in water [J]. Water Purification Technology, 2020, (7): 130-138.) The disadvantage of this study is that the barium titanate for piezoelectric catalysis and the divalent iron ions for Fenton effect do not play a synergistic role, and the degradation rate is low. Compared with the present invention, the present invention constructs a heterojunction in barium titanate and ferrous iron tetroxide. In the catalytic process, piezoelectric photocatalysis and Fenton effect can play a good synergistic role, which greatly improves the catalytic reaction rate. Summary of the invention

[0010] The purpose of the present invention is to provide a catalytic material with excellent performance and recyclability, a preparation method and application, namely, a BaTiO3@Fe3O4 composite material. In order to overcome the problems existing in the prior art, the present invention has a simple preparation process, is easy to recycle and can be reused, has the performance of highly efficient degradation of organic dyes, and its catalytic effect is far superior to pure phase barium titanate and ferrosoferric oxide.

[0011] In order to achieve the above object, the present invention adopts the following technical scheme: A method for preparing a BaTiO3@Fe3O4 composite material comprises the following steps: Step 1: Prepare dice-shaped barium titanate powder by hydrothermal method through centrifugal drying and grinding.

[0012] Step 2: Using a solvothermal method, in-situ growing ferroferric oxide on the prepared barium titanate powder forms a core-shell structure.

[0013] Step 3: The solution obtained after solvent heating is centrifuged, dried and ground to obtain a BaTiO3@Fe3O4 composite catalyst.

[0014] Furthermore, step one is specifically to add BaCl2·2H2O and TiCl4 into NaOH solution by hydrothermal method, transfer the mixture into a reaction kettle after sufficient stirring, and obtain barium titanate powder under high temperature and high pressure.

[0015] Furthermore, in step 1, the concentration of NaOH solution is 1-4 mol / L, the reaction temperature is 180-240° C., and the reaction time is 18-28 h.

[0016] Furthermore, in step 1, the molar ratio of BaCl2·2H2O to TiCl4 is 1.2-2.

[0017] Furthermore, step 2 specifically includes adding BaTiO3, FeCl3·6H2O, and anhydrous sodium acetate into ethylene glycol, and transferring the mixture into a reaction kettle for solvothermal reaction after sufficient stirring.

[0018] Furthermore, the concentration of anhydrous sodium acetate in the reactor in step 2 is 0.5-4 mol / L.

[0019] Furthermore, in step 2, the molar ratio of BaTiO3 to FeCl3·6H2O is 1:3-3:1.

[0020] Furthermore, the reaction temperature of step 2 is set to 180-220° C., and the reaction time is 6-12 h.

[0021] Furthermore, in step 1, the centrifugal speed is 5000-10000 r / min, the centrifugal time is 2-6 min, and after washing three times with anhydrous ethanol, it is transferred to an oven for insulation at a temperature of 50-80°C for 6-14h.

[0022] Furthermore, in step three, the centrifugal speed is 5000-10000 r / min, the centrifugal time is 2-6 min, and after washing three times with anhydrous ethanol, it is transferred to an oven for insulation at a temperature of 50-80°C for 6-14h.

[0023] Furthermore, analytically pure raw materials were used for the preparation.

[0024] Application: Furthermore, the BaTiO3@Fe3O4 catalytic material has a core-shell structure. Under the action of simulated sunlight and mechanical energy, the BaTiO3@Fe3O4 catalytic material is added to wastewater containing organic dyes to catalytically degrade the organic dyes. Furthermore, the simulated sunlight has a current of 1-30A and a distance between the light source and the pollutant of 1-50cm.

[0025] Furthermore, the mechanical energy source is an ultrasonic cleaning machine with a power of 80-400W.

[0026] Furthermore, the corresponding catalyst concentration is 1 mg / L-10 g / L, the dye is rhodamine B, methyl orange, methylene blue, methyl blue, malachite green, etc., and the dye concentration is 0.1 ppm-200 ppm; corresponding catalytic performance: degradation rate reaches 50%-100%.

[0027] In summary, the present invention has the following advantages: (1) The present invention successfully prepared a BaTiO3@Fe3O4 composite material with a core-shell structure through two-step hydrothermal treatment. The material has corresponding catalytic properties under the action of light and mechanical energy, and the degradation rate of 5 ppm rhodamine B solution reaches 100% in 9 minutes, and the degradation rate reaches 0.48 min -1 .

[0028] (2) The composite material of the present invention is environmentally friendly, easily recyclable and reusable, and the degradation rate still reaches 70% after four rounds of degradation of 10 ppm rhodamine B solution.

[0029] (3) The composite material of the present invention has wide applicability, has excellent catalytic effect under different pH values ​​and different pollutants, has a simple preparation process, low material cost, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings in the specification are used to provide further understanding of the present invention and constitute a part of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0031] Figure 1 X-ray diffraction patterns of the materials prepared in Comparative Examples 1-2 and Examples 1-3.

[0032] Figure 2 The degradation efficiency and pseudo-first-order kinetic curves of the materials prepared in Comparative Examples 1-3 and Examples 1-3 for 5 ppm Rhodamine B solution under simulated sunlight and ultrasonic vibration are shown.

[0033] Figure 3 This is the absorbance curve of Example 4 during the degradation process of 10 ppm malachite green solution.

[0034] Figure 4 This is the absorbance curve of Example 5 during the degradation process of 10 ppm methylene blue solution.

[0035] Figure 5 This is a scanning electron microscope image of the material prepared in Example 1.

[0036] Figure 6This is a scanning electron microscope image of the material prepared in Comparative Example 1.

[0037] Figure 7 This is a curve chart showing the absorbance variation over time of the material prepared in Example 1 when a 10 ppm Rhodamine B solution is degraded through 4 recycling cycles under light and ultrasonic vibration. DETAILED DESCRIPTION

[0038] In order to make the contents of the present invention easier to understand, the present invention is further described below in conjunction with embodiments.

[0039] A BaTiO3@Fe3O4 catalytic material with excellent performance and recyclability and a preparation method thereof, wherein the specific steps are as follows: Step 1: Take 6.4g NaOH and dissolve it in 80ml deionized water, then add 11.4g BaCl2·2H2O, slowly add 4.25ml TiCl4 after magnetic stirring, and then transfer it to a hydrothermal reactor after magnetic stirring for 60min. The reactor is placed in a 210℃ oven and kept warm for 24h. After the reaction is completed, the suspension is centrifuged, washed with anhydrous ethanol, and finally dried in a 60℃ oven to obtain BaTiO3 powder.

[0040] Step 2: Add the BaTiO3 powder obtained in step 1 to 80 ml of ethylene glycol, add 7.2 g of anhydrous sodium acetate after magnetic stirring for 60 minutes, add FeCl3·6H2O after magnetic stirring for 60 minutes, wherein n(BaTiO3):n(FeCl3·6H2O)=1:3; 1:1; 3:1, transfer to a hydrothermal reactor after magnetic stirring for 60 minutes, place the reactor in a 200°C oven for 8 hours, centrifuge the suspension after the reaction is completed, wash with anhydrous ethanol, and finally dry in a 60°C oven to obtain BaTiO3@Fe3O4 powder.

[0041] The present invention forms a heterostructure by constructing BaTiO3@Fe3O4, and the interface of the heterojunction can provide new activation sites for catalytic reactions. Reactants can be more easily adsorbed, activated or dissociated at these sites, thereby reducing the energy barrier of the reaction. In addition, the heterojunction structure can also promote the efficient transfer of electrons in catalytic reactions. In addition, through the action of light and external mechanical energy, the BaTiO3 and Fe3O4 heterojunction can promote the separation of carriers. The carriers have high reactivity and trigger a series of redox reactions. In the catalytic process, due to the Fenton effect, iron ions (Fe 2+ ) reacts with trace amounts of hydrogen peroxide (H2O2) produced during the catalytic process to produce hydroxyl radicals (·OH), which are strong oxidants that can effectively oxidize and degrade a variety of organic pollutants. The synergistic effect of photo-piezoelectric catalysis and Fenton reaction is used to further improve the catalytic performance of the composite.

[0042] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.

[0043] The following detailed description is the description of the embodiments, and is intended to provide further detailed description of the present invention. Unless otherwise specified, all technical terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used in the present invention are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present invention.

[0044] Comparative Example 1 BaTiO3 is prepared by hydrothermal method, and the specific steps are as follows: Step 1: Dissolve 6.4 g NaOH in 80 ml deionized water.

[0045] Step 2: Add 11.4 g BaCl2·2H2O to the above solution and stir magnetically for 60 min.

[0046] Step 3: Slowly add 4.25 ml of TiCl4 liquid to the above solution, and then transfer it to the hydrothermal reactor after magnetic stirring for 60 minutes.

[0047] Step 4: Place the reactor in an oven at 210°C for 24 hours.

[0048] Step 5: After the reaction is completed, the suspension is centrifuged, washed with anhydrous ethanol, and finally dried in an oven at 60°C to obtain BaTiO3 powder.

[0049] Step 6: Weigh 50 mg of BaTiO3 powder and pour it into 50 ml of 5 ppm Rhodamine B solution. After 30 minutes of adsorption and desorption equilibrium in a dark environment, transfer it to a 300 W ultrasonic cleaning machine. At the same time, add an 18A simulated sunlight light source 15 cm above the solution. During the catalytic process, take 3 ml of the solution at regular intervals and test its absorbance using a UV spectrophotometer.

[0050] Comparative Example 2 Fe3O4 is prepared by hydrothermal method, and the specific steps are as follows: Step 1: Add 7.2 g of anhydrous sodium acetate to 80 ml of ethylene glycol and stir magnetically for 60 min.

[0051] Step 2: Add 0.819 g FeCl3·6H2O to the above solution, and transfer to a hydrothermal reactor after magnetic stirring for 60 min.

[0052] Step 3: Place the reactor in an oven at 200°C for 8 hours.

[0053] Step 4: After the reaction is completed, the suspension is centrifuged, washed with anhydrous ethanol, and finally dried in an oven at 60°C to obtain Fe3O4 powder.

[0054] Step 5: Weigh 50 mg of Fe3O4 powder and pour it into 50 ml of 5 ppm Rhodamine B solution. After 30 minutes of adsorption and desorption equilibrium in a dark environment, transfer it to a 300 W ultrasonic cleaning machine. At the same time, add an 18A simulated sunlight light source 15 cm above the solution. During the catalytic process, take 3 ml of the solution at regular intervals and test its absorbance using a UV spectrophotometer.

[0055] Comparative Example 3 BaTiO3 and Fe3O4 are prepared separately by hydrothermal method and mechanically mixed. The specific steps are as follows: Step 1: Dissolve 6.4g NaOH in 80ml deionized water, add 11.4g BaCl2·2H2O, stir magnetically for 60min, slowly drop 4.25ml TiCl4 liquid, stir magnetically for 60min, transfer to a hydrothermal reactor, and place the reactor in a 210℃ oven for 24h. After the reaction is completed, centrifuge the suspension, wash with anhydrous ethanol, and finally dry in a 60℃ oven to obtain BaTiO3 powder.

[0056] Step 2: Add 7.2g of anhydrous sodium acetate to 80ml of ethylene glycol, stir magnetically for 60min, then add 0.819g of FeCl3·6H2O to the solution, stir magnetically for 60min, transfer to a hydrothermal reactor, and place the reactor in a 200℃ oven for 8h. After the reaction is completed, centrifuge the suspension, wash with anhydrous ethanol, and finally dry in a 60℃ oven to obtain Fe3O4 powder.

[0057] Step 3: Take 0.2g of BaTiO3 and Fe3O4 prepared in step 1 and step 2, add them into 60ml of deionized water, stir for 60min, wash by centrifugation and dry in a 60℃ oven.

[0058] Step 4: Weigh a total of 50 mg of BaTiO3 and Fe3O4 (molar ratio 1:1) and pour them into 50 ml of 5 ppm Rhodamine B solution. After 30 minutes of adsorption and desorption equilibrium in a dark environment, transfer them to a 300 W ultrasonic cleaning machine. At the same time, add an 18A simulated sunlight light source 15 cm above the solution. During the catalytic process, take 3 ml of the solution at regular intervals and test its absorbance using a UV spectrophotometer.

[0059] Example 1 Step 1: Take 6.4g NaOH and dissolve it in 80ml deionized water, then add 11.4g BaCl2·2H2O, slowly add 4.25ml TiCl4 after magnetic stirring, and then transfer it to a hydrothermal reactor after magnetic stirring for 60min. The reactor is placed in a 210℃ oven and kept warm for 24h. After the reaction is completed, the suspension is centrifuged, washed with anhydrous ethanol, and finally dried in a 60℃ oven to obtain BaTiO3 powder.

[0060] Step 2: Add the BaTiO3 powder obtained in step 1 to 80 ml of ethylene glycol, add 7.2 g of anhydrous sodium acetate after magnetic stirring for 60 minutes, add FeCl3·6H2O after magnetic stirring for 60 minutes, wherein n(BaTiO3):n(FeCl3·6H2O)=3:1, transfer to a hydrothermal reactor after magnetic stirring for 60 minutes, place the reactor in a 200°C oven for 8 hours, centrifuge the suspension after the reaction is completed, wash with anhydrous ethanol, and finally dry in a 60°C oven to obtain 0.75BaTiO3@0.25Fe3O4 powder.

[0061] Step 3: Weigh 50 mg of 0.75BaTiO3@0.25Fe3O4 powder and pour it into 50 ml of 5 ppm Rhodamine B solution. After 30 minutes of adsorption and desorption equilibrium in a dark environment, transfer it to a 300 W ultrasonic cleaning machine. At the same time, add an 18A simulated sunlight light source 15 cm above the solution. During the catalytic process, take 3 ml of the solution at regular intervals and test its absorbance using a UV spectrophotometer.

[0062] Example 2 Step 1: Take 6.4g NaOH and dissolve it in 80ml deionized water, then add 11.4g BaCl2·2H2O, slowly add 4.25ml TiCl4 after magnetic stirring, and then transfer it to a hydrothermal reactor after magnetic stirring for 60min. The reactor is placed in a 210℃ oven and kept warm for 24h. After the reaction is completed, the suspension is centrifuged, washed with anhydrous ethanol, and finally dried in a 60℃ oven to obtain BaTiO3 powder.

[0063] Step 2: Add the BaTiO3 powder obtained in step 1 to 80 ml of ethylene glycol, add 7.2 g of anhydrous sodium acetate after magnetic stirring for 60 minutes, add FeCl3·6H2O after magnetic stirring for 60 minutes, wherein n(BaTiO3):n(FeCl3·6H2O)=1:1, transfer to a hydrothermal reactor after magnetic stirring for 60 minutes, place the reactor in a 200°C oven for 8 hours, centrifuge the suspension after the reaction is completed, wash with anhydrous ethanol, and finally dry in a 60°C oven to obtain 0.5BaTiO3@0.5Fe3O4 powder.

[0064] Step 3: Weigh 50 mg of 0.5BaTiO3@0.5Fe3O4 powder and pour it into 50 ml of 5 ppm Rhodamine B solution. After 30 minutes of adsorption and desorption equilibrium in a dark environment, transfer it to a 300 W ultrasonic cleaning machine. At the same time, add an 18A simulated sunlight light source 15 cm above the solution. During the catalytic process, take 3 ml of the solution at regular intervals and test its absorbance using a UV spectrophotometer.

[0065] Example 3 Step 1: Take 6.4g NaOH and dissolve it in 80ml deionized water, then add 11.4g BaCl2·2H2O, slowly add 4.25ml TiCl4 after magnetic stirring, and then transfer it to a hydrothermal reactor after magnetic stirring for 60min. The reactor is placed in a 210℃ oven and kept warm for 24h. After the reaction is completed, the suspension is centrifuged, washed with anhydrous ethanol, and finally dried in a 60℃ oven to obtain BaTiO3 powder.

[0066] Step 2: Add the BaTiO3 powder obtained in step 1 to 80 ml of ethylene glycol, add 7.2 g of anhydrous sodium acetate after magnetic stirring for 60 minutes, add FeCl3·6H2O after magnetic stirring for 60 minutes, wherein n(BaTiO3):n(FeCl3·6H2O)=1:3, transfer to a hydrothermal reactor after magnetic stirring for 60 minutes, place the reactor in a 200°C oven for 8 hours, centrifuge the suspension after the reaction is completed, wash with anhydrous ethanol, and finally dry in a 60°C oven to obtain 0.25BaTiO3@0.75Fe3O4 powder.

[0067] Step 3: Weigh 50 mg of 0.25BaTiO3@0.75Fe3O4 powder and pour it into 50 ml of 5 ppm Rhodamine B solution. After 30 minutes of adsorption and desorption equilibrium in a dark environment, transfer it to a 300 W ultrasonic cleaning machine. At the same time, add an 18A simulated sunlight light source 15 cm above the solution. During the catalytic process, take 3 ml of the solution at regular intervals and test its absorbance using a UV spectrophotometer.

[0068] Example 4 Step 1: Take 6.4g NaOH and dissolve it in 80ml deionized water, then add 11.4g BaCl2·2H2O, slowly add 4.25ml TiCl4 after magnetic stirring, and then transfer it to a hydrothermal reactor after magnetic stirring for 60min. The reactor is placed in a 210℃ oven and kept warm for 24h. After the reaction is completed, the suspension is centrifuged, washed with anhydrous ethanol, and finally dried in a 60℃ oven to obtain BaTiO3 powder.

[0069] Step 2: Add the BaTiO3 powder obtained in step 1 to 80 ml of ethylene glycol, add 7.2 g of anhydrous sodium acetate after magnetic stirring for 60 minutes, add FeCl3·6H2O after magnetic stirring for 60 minutes, wherein n(BaTiO3):n(FeCl3·6H2O)=3:1, transfer to a hydrothermal reactor after magnetic stirring for 60 minutes, place the reactor in a 200°C oven for 8 hours, centrifuge the suspension after the reaction is completed, wash with anhydrous ethanol, and finally dry in a 60°C oven to obtain 0.75BaTiO3@0.25Fe3O4 powder.

[0070] Step 3: Weigh 50 mg of 0.75BaTiO3@0.25Fe3O4 powder and pour it into 50 ml of 10 ppm malachite green solution. After 30 minutes of adsorption and desorption equilibrium in a dark environment, transfer it to a 300 W ultrasonic cleaning machine. At the same time, add an 18A simulated sunlight light source 15 cm above the solution. During the catalytic process, take 3 ml of the solution at intervals and test its absorbance using a UV spectrophotometer.

[0071] Example 5 Step 1: Take 6.4g NaOH and dissolve it in 80ml deionized water, then add 11.4g BaCl2·2H2O, slowly add 4.25ml TiCl4 after magnetic stirring, and then transfer it to a hydrothermal reactor after magnetic stirring for 60min. The reactor is placed in a 210℃ oven and kept warm for 24h. After the reaction is completed, the suspension is centrifuged, washed with anhydrous ethanol, and finally dried in a 60℃ oven to obtain BaTiO3 powder.

[0072] Step 2: Add the BaTiO3 powder obtained in step 1 to 80 ml of ethylene glycol, add 7.2 g of anhydrous sodium acetate after magnetic stirring for 60 minutes, add FeCl3·6H2O after magnetic stirring for 60 minutes, wherein n(BaTiO3):n(FeCl3·6H2O)=3:1, transfer to a hydrothermal reactor after magnetic stirring for 60 minutes, place the reactor in a 200°C oven for 8 hours, centrifuge the suspension after the reaction is completed, wash with anhydrous ethanol, and finally dry in a 60°C oven to obtain 0.75BaTiO3@0.25Fe3O4 powder.

[0073] Step 3: Weigh 50 mg of 0.75BaTiO3@0.25Fe3O4 powder and pour it into 50 ml of 10 ppm methylene blue solution. After 30 minutes of adsorption and desorption equilibrium in a dark environment, transfer it to a 300 W ultrasonic cleaning machine. At the same time, add an 18A simulated sunlight light source 15 cm above the solution. During the catalytic process, take 3 ml of the solution at intervals and test its absorbance using a UV spectrophotometer.

[0074] from Figure 1 It can be seen that the diffraction peaks of the composite materials prepared in all examples are consistent with the standard cards of BaTiO3 (PDF#89-1428) and Fe3O4 (PDF#88-0866), and no other impurity phases appear. Figure 2 It can be seen that the catalytic performance of the embodiment is better than that of the comparative example under the conditions of simulated sunlight and external 300W mechanical energy. The catalytic efficiency of the BaTiO3 and Fe3O4 mixed powder is much lower than that of the BaTiO3@Fe3O4 composite material, indicating that a heterojunction is formed between the BaTiO3@Fe3O4 core-shell structure, which effectively separates the carriers and promotes the efficient transfer of electrons. The performance is best when n(BaTiO3):n(FeCl3·6H2O)=3:1, and the rate constant reaches 0.483min -1 . Figure 3 Figure 4 The absorbance curves of the solutions during the catalytic process of 0.75BaTiO3@0.25Fe3O4 on 10ppm malachite green and 10ppm methylene blue are shown respectively. The catalyst of the present invention has high universality for dye degradation, and not only has a high degradation rate and fast degradation rate for rhodamine B solution, but also has excellent degradation effects on malachite green and methylene blue solutions. Figure 6 This is the SEM of the barium titanate powder prepared in Comparative Example 1, the particle size is between 150-200nm, and the surface is smooth and dice-shaped. Figure 5 This is the SEM of the composite material prepared in Example 1. The surface morphology of the material becomes rough because the second phase Fe3O4 is successfully grown on the surface of BaTiO3. The particle size of Fe3O4 is about 50nm. A core-shell structure with BaTiO3 as the core and Fe3O4 as the shell is successfully constructed. Figure 7 After four rounds of degradation, recovery and recycling of the 10 ppm rhodamine B solution, the 0.75BaTiO3@0.25Fe3O4 composite material of the present invention can still achieve a degradation rate of 70%.

[0075] Table 1 shows some reported catalyst types and catalytic performances. Compared with the present invention, the BaTiO3@Fe3O4 composite material prepared by the present invention is environmentally friendly, easily recyclable and reusable, has a simple preparation process, low material cost, and is suitable for industrial production. The prepared BaTiO3@Fe3O4 composite material has more active sites, high photogenerated carrier separation efficiency, and has the performance of efficient catalytic degradation of organic dyes, and is expected to be applied to sewage treatment and other fields.

[0076] Table 1 Comparison of catalytic performance of related catalysts in the examples and related reports Note: [1] Shaanxi University of Science and Technology. Preparation method of barium titanate / iron oxyhydroxide photocatalyst: CN202110872559.3[P]. 2021-09-28. [2] Qingdao University of Science and Technology. Preparation method and application of BaTiO3 / GDY / Au piezoelectric enhanced photocatalyst: CN 117942997[P]. A2024.01.29 [3] Wang Y , Liu L , ZhaoW ,et al.Spontaneous polarization offerroelectric BaTiO3 / ZnO heterostructures with enhanced performance in aFenton-like catalytic reaction[J].Ceramics International,2022,48(2):2726-2735.DOI:10.1016 / j.ceramint.2021.10.059. [4] Fu B, Li J, Jiang H, et al. Enhanced piezotronics by single-crystalline ferroelectrics for uniformly strengthening the piezo-photocatalysis of electrospun BaTiO3@TiO2nanofibers[J]. Nanoscale, 2022,14(38):14073-14081. [5] Mushtaq F, Chen [6] Zhang Sen. Degradation of carbamazepine in water by low-frequency ultrasound-driven BaTiO3 piezoelectric-Fenton system[J]. Water Purification Technology, 2020, (7): 130-138. The embodiments described above are only preferred technical solutions of the present invention and should not be regarded as limitations of the present invention. The embodiments and features in the embodiments of the present application can be arbitrarily combined with each other without conflict. The protection scope of the present invention shall be the technical solutions recorded in the claims, including the equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.

Claims

1. Application of BaTiO3@Fe3O4 catalytic material in catalytic degradation of organic dyes, characterized in that: The BaTiO3@Fe3O4 catalytic material has a core-shell structure. Under the action of simulated sunlight and mechanical energy, the BaTiO3@Fe3O4 catalytic material is added to wastewater containing organic dyes to catalytically degrade the organic dyes. The preparation method of the BaTiO3@Fe3O4 catalytic material comprises the following steps: Step 1: preparing cubic dice-shaped barium titanate powder by hydrothermal method through centrifugal drying and grinding; Step 2: In-situ growth of ferroferric oxide on the prepared barium titanate powder by a solvothermal method to form a core-shell structure; Step 3: The solution obtained after solvothermal treatment is centrifugally dried and ground to obtain BaTiO3@Fe3O4 catalytic material.

2. The use according to claim 1, characterized in that: Step 1 is specifically as follows: BaCl2·2H2O and TiCl4 are added to the NaOH solution, and after being fully stirred, the solution is transferred to a reaction kettle and subjected to high temperature and high pressure to obtain barium titanate powder.

3. The use according to claim 2, characterized in that: In step 1, the concentration of NaOH solution is 1-4 mol / L, the reaction temperature is 180-240° C., and the reaction time is 18-28 h.

4. The use according to claim 2, characterized in that: In step 1, the molar ratio of BaCl2·2H2O to TiCl4 is 1.2-2.

5. The use according to claim 1, characterized in that: Step 2 specifically includes: adding BaTiO3, FeCl3·6H2O and anhydrous sodium acetate into ethylene glycol, and transferring the mixture into a reaction kettle after sufficient stirring to carry out a solvent thermal reaction.

6. The use according to claim 5, characterized in that: The concentration of anhydrous sodium acetate in the reaction kettle of step 2 is 0.5-4 mol / L.

7. The use according to claim 5, characterized in that: In step 2, the molar ratio of BaTiO3 to FeCl3·6H2O is 1:3-3:

1.

8. The use according to claim 5, characterized in that: In step 2, the reaction temperature is 180-220° C. and the reaction time is 6-12 h.

9. The use according to claim 1, characterized in that: In step 1 and step 3, the centrifugal speed is 5000-10000 r / min, the centrifugal time is 2-6 min, and after washing three times with anhydrous ethanol, the mixture is transferred to an oven for heat preservation at a temperature of 50-80° C. for 6-14 h.

10. The use according to claim 1, characterized in that: The mechanical energy source is an ultrasonic cleaning machine with a power of 80-400W; the organic dyes include rhodamine B, methyl orange, methylene blue, methyl blue, and malachite green.

Citation Information

Patent Citations

  • Preparation method of barium titanate / iron oxyhydroxide photocatalyst

    CN113441145A

  • Preparation method and application of BaTiO3 / GDY / Au piezoelectric enhanced photocatalyst

    CN117942997A